An Evaluation on the Effects of Location on Residential Property Value in Awka, Anambra State, Nigeria - Onyejiaka, J. C.; Ibedu , E. A.; Ewah, M. A. (International Journal of Real Estate, 2025)
This study investigates the effect of location on residential property values in Awka, with a focus on key locational factors, proximity to urban amenities, infrastructural development, and spatial distribution of property values. The objectives of the study are to: Identify the locational factors that influence residential property values in Awka; examine the relationship between proximity to urban amenities and residential property values; assess how infrastructural development affects the value of residential properties; evaluate the spatial distribution of residential property values across selected neighborhoods in Awka. The research adopted a quantitative approach using structured, closed-ended questionnaires administered to a sample of 63 respondents, out of which 58 were duly completed and analyzed. Descriptive statistics were employed to interpret the data. Findings revealed that both location and proximity to urban amenities such as schools, healthcare facilities, markets, and public transport plays a more significant role in determining residential property values. Furthermore, infrastructural development, including road networks, electricity, and water supply, was found to contribute positively to property valuation. Spatially, properties in central and well-developed areas command higher values than those in peripheral zones. The study concludes that urban amenities and infrastructure together with location are critical drivers of residential property value in Awka and recommends that urban planners, developers, and policymakers prioritize the provision of accessible services in all areas to ensure equitable property value growth.